2003
DOI: 10.1017/s1481803500008125
|View full text |Cite
|
Sign up to set email alerts
|

Neurologically normal survival after fibrinolysis during prolonged cardiac arrest: case report and discussion

Abstract: Cardiac arrest secondary to pulmonary embolism is a devastating condition with a high mortality rate. It is currently unclear whether fibrinolysis (thrombolysis) is beneficial in this setting. We report the case of a 28-year-old woman with a pulmonary embolism who developed return of pulses following the administration of tissue plasminogen activator after 38 minutes of pulseless electrical activity cardiac arrest. She went on to make a full neurologic and cardiopulmonary recovery. This case is discussed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…3 Published cases revealed good or intact neurological status for the majority of survivors, even in cases of prolonged CPR up to 90 minutes and delayed fibrinolytic administration up to 60 minutes. 4,14,15,[18][19][20][21][23][24][25][27][28][29]33,35,37 These findings are consistent with experimental studies that showed that fibrinolytics may reduce the cerebral no-reflow phenomenon and improve microcirculatory reperfusion. 40,41 The occurrence of major bleeding complications (total, intracranial, and fatal) is a serious concern of fibrinolysis during CPR.…”
Section: Discussionsupporting
confidence: 88%
“…3 Published cases revealed good or intact neurological status for the majority of survivors, even in cases of prolonged CPR up to 90 minutes and delayed fibrinolytic administration up to 60 minutes. 4,14,15,[18][19][20][21][23][24][25][27][28][29]33,35,37 These findings are consistent with experimental studies that showed that fibrinolytics may reduce the cerebral no-reflow phenomenon and improve microcirculatory reperfusion. 40,41 The occurrence of major bleeding complications (total, intracranial, and fatal) is a serious concern of fibrinolysis during CPR.…”
Section: Discussionsupporting
confidence: 88%
“…2 It is impossible to know if the thrombolytic agent played a role in our patient's outcome; however, two randomized controlled trials have shown that thrombolysis during CPR is not beneficial in an undifferentiated population. 3,4 What is noteworthy about our case is the use of ECMO and the probable role it played.…”
Section: Discussionmentioning
confidence: 99%